2012
DOI: 10.1073/pnas.1207816109
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2deficiency uncovers a dominant role for thromboxane A2in house dust mite-induced allergic pulmonary inflammation

Abstract: Prostaglandin E 2 (PGE 2 ) is an abundant lipid inflammatory mediator with potent but incompletely understood anti-inflammatory actions in the lung. Deficient PGE 2 generation in the lung predisposes to airway hyperresponsiveness and aspirin intolerance in asthmatic individuals. PGE 2 -deficient ptges −/− mice develop exaggerated pulmonary eosinophilia and pulmonary arteriolar smoothmuscle hyperplasia compared with PGE 2 -sufficient controls when challenged intranasally with a house dust mite extract. We now d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 57 publications
2
46
0
Order By: Relevance
“…4C). Short-term TP receptor blockade had no effect on histologic indices of inflammation, whereas tpr deletion markedly impaired the development of these features as in our previous study (28). Discussion AERD accounts disproportionately for severe asthma and chronic rhinosinusitis (3,4).…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 77%
See 3 more Smart Citations
“…4C). Short-term TP receptor blockade had no effect on histologic indices of inflammation, whereas tpr deletion markedly impaired the development of these features as in our previous study (28). Discussion AERD accounts disproportionately for severe asthma and chronic rhinosinusitis (3,4).…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 77%
“…Ptges −/− mice develop marked eosinophildominated bronchovascular cellular infiltrates (>75% of BAL fluid cells) with lesser numbers of neutrophils (28,35). AERD is also associated with marked eosinophilia of the respiratory mucosa (44), often without evidence of sensitization to allergens.…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
See 2 more Smart Citations
“…COX-2 inhibitors reduce mucosal damage, which further indicates the role of prostaglandins in tissue damage and inflammation reactions (Zheng et al 2012). PTGES catalyzes the isomerization of PGH2 to PGE2, and the latter plays an important role in inflammation (Liu et al 2012a), cell growth, and transformation (Sasaki et al 2012). In the current study, we found that the NF-κB, iNOS, and TNF-α mRNA levels of heart tissue were significantly increased (P < 0.05) in stress groups.…”
Section: Discussionmentioning
confidence: 99%